2020
DOI: 10.2147/ott.s233256
|View full text |Cite|
|
Sign up to set email alerts
|

<p>Long Non-Coding RNA HAND2-AS1 Inhibits Growth and Migration of Gastric Cancer Cells Through Regulating the miR-590-3p/KCNT2 Axis</p>

Abstract: Introduction: Long non-coding RNAs (lncRNAs) are regarded as crucial regulators for cancer initiation and progression. Heart and Neural Crest Derivatives Expressed 2 antisense RNA 1 (HAND2-AS1) was recently proposed to function as tumor suppressor in several human cancers. However, its role in gastric cancer (GC) remains unclear. Methods: HAND2-AS1 expression in GC tissues and normal tissues was analyzed at GEPIA (a web server for gene expression profiling analysis). Moreover, RT-qPCR method was utilized to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“… 24 LncRNA FTX expression in GC is also up-regulated, and FTX can promote GC proliferation and invasion by adsorbing miR-144 and up-regulating ZFX ; 25 conversely, as a tumor suppressor, lncRNA HAND2-AS1 inhibits the proliferation and migration of GC cells through modulating miR-590-3p/ KCNT2 axis. 26 In this study, we verified that CTBP1-AS2 was a molecular sponge for miR-139-3p. Furthermore, functional experiments illustrated that CTBP1-AS2 promoted cell proliferation and suppressed apoptosis by inhibiting miR-139-3p expression.…”
Section: Discussionsupporting
confidence: 63%
“… 24 LncRNA FTX expression in GC is also up-regulated, and FTX can promote GC proliferation and invasion by adsorbing miR-144 and up-regulating ZFX ; 25 conversely, as a tumor suppressor, lncRNA HAND2-AS1 inhibits the proliferation and migration of GC cells through modulating miR-590-3p/ KCNT2 axis. 26 In this study, we verified that CTBP1-AS2 was a molecular sponge for miR-139-3p. Furthermore, functional experiments illustrated that CTBP1-AS2 promoted cell proliferation and suppressed apoptosis by inhibiting miR-139-3p expression.…”
Section: Discussionsupporting
confidence: 63%
“…In GC, TCEAL7 was revealed to be decreased expression and correlated with prognosis of cancer patients [20] . Our previous work suggested that HAND2-AS1 could regulate GC cell growth and migration via regulating the miR-590-3p/KCNT2 axis [21] . Here, we presented a novel regulatory mechanism for roles of HAND2-AS1 in GC progression.…”
Section: Discussionmentioning
confidence: 99%
“…Its anti-tumorigenic effect is mediated by downregulating NMU, an oncogenic protein in EEC [ 70 ]. In GC cells, HAND2-AS1 expression is decreased; however, overexpression of HAND2-AS1 is capable of inhibiting GC cell proliferation and promoting their apoptosis by functioning as a ceRNA that binds with miR-590-3p [ 71 ]. Another study demonstrated that HAND2-AS1 can also exert its tumor suppressive role through the miR-769-5p/ TCEAL7 axis in GC [ 72 ].…”
Section: Antisense Lncrnas Act As Tumor Suppressorsmentioning
confidence: 99%